Entre o amor, o ódio e o humor: representações da docência e da relação pedagógica em memes compartilhados no Facebook - Santos, Yara Magalhães dos (2021)
In the present study, we propose an investigation about how the relationship between teachers and students is presented in memes shared on the social network Facebook. To this end, we collected a sample of seventy-two images, whose characteristics allowed them to be categorized as internet memes. Our objective was to identify and analyze how the pedagogical relationship and teaching itself were represented in these memes. To answer the research problem, we carried out bibliographical research, which aimed to conceptualize and analyze the object of study, and also empirical research with a qualitative approach, which was based on the analysis of the form and content of the raised images. Understanding the object of study as a phenomenon of digital media culture, we rely on theoretical foundations of Critical Theory, more specifically on those focused on the debate on the cultural industry, and we analyze the connections between cyberculture and the production of socially shared representations. As a complement, we also rely on some elements of Freudian Psychoanalysis to discuss issues related to exposure and manifestation in social networks. From the data analysis, we established four central axes of analysis for the representations present in the images. The first of them indicates that the relationship between teachers and students is represented in an ambivalent way, since students' feelings towards their teachers move between love and hate, admiration and hostility, reverence and sarcasm. The research results revealed that the ambivalence of the pedagogical link materializes in the ironic ambiguity of the content of the images. In the second axis of analysis, we defend that some memes present images of teachers sometimes associated with the ideas of suffering, misfortune and illness, sometimes with the image of the executioner, suggesting their enjoyment in the face of students' suffering. We join these two representations to discuss the updating of taboos in relation to the teaching profession, ideas that are frequent in the illustrations shared on the internet, including by the teachers themselves. In the third axis of analysis, we point out memes that present insults directed at teachers, suggesting that these images manifest cyberbullying actions against them on social networks, a phenomenon mitigated by the jocularity of the images, but which does not fail to indicate the symbolic violence that involves exposure and ridicule of teachers in the network. Finally, we analyze the role of humor in the construction of these representations, which suggests an equally ambiguous operation, which can both trivialize and desensitize the construction of stereotypes and violent manifestations, as well as subverting and reframing the teachers' view of the dilemmas that affect them daily.